Polszczyzna młodej inteligencji na przykładzie tekstów popularyzujących naukę - Sagan-Bielawa, Mirosława (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
The article refers to the concept of intelligentsia as a social group which exerts significant influence on Polish standard patterns. Although the term intelligentsia is vague and questionable, it is well-established term in Polish linguistics, especially in sociolinguistics. Author argues that science communicators (young professional researchers, science journalists, PhD students) represent the young intelligentsia, because these well-educated people pursue their intellectual development and they have sense of public duty. The article examines standard of popular science texts in Internet, new tendencies in written Polish and attitude of young intelligentsia toward traditional linguistic norm. The errors (esp. punctuation and syntax) exemplify impact of technological changes and phenomenon of secondary orality. It would be useful for science communicators to edit carefully their texts. Both researchers and journalists need to improve their writing skills permanently. Nevertheless it must be emphasized that school education and competent teachers seem to have important influence on the linguistic patterns.
Keywords: science communication; language change; linguistic prescription; young generation